Advances of nanopore direct sequencing technology and bioinformatics analysis for cell-free DNA detection and its clinical applications in cancer liquid biopsy - Tan, Jiaxin; Wu, Zetong; Zhu, Yunya; Miao, Biyuan; Xu, Daofeng; Gu, Jia; Hu, Maohong; Xu, Pingping; Wan, Shaogui (Frontiers in Molecular Biosciences, 2025)
Cell-free DNA (cfDNA) containing cancer information has become a key biomarker for cancer liquid biopsy. Current next-generation sequencing (NGS) technology for cfDNA detection often fail to capture multiomics information, such as fragmentomics, epigenetics, and genetics, in a single assay. Recently, Oxford Nanopore Technologies (ONT) has demonstrated advantages in acquiring cfDNA’s multiomics data by a single sequencing run. In this review, we summarize the recent advancements in library preparation and bioinformatic analyses for cfDNA methylation, copy number variations (CNVs), as well as other biomarkers derived from cfDNA sequencing on the ONT platform. Furthermore, we highlight the latest research progress in the clinical applications of multi-dimensional cfDNA features and outline the future directions of nanopore cfDNA sequencing. Overall, this review updates the understanding of cfDNA detection using nanopore sequencing, providing valuable insights for studies of cfDNA in cancer.